Peran Mahasiswa Dan Masyarakat Dalam Mengurangi Resiko Bencana Alam Yang Terjadi Di Desa Sibalaya Barat - Hariani Hariani; Rahdyanti Rahdyanti; Moh Ali Murad; Risnawati Risnawati (Jurnal Ekonomi Manajemen Akuntansi, 2023)
Efforts in disaster risk reduction have not been carried out optimally. In this case, the socialization of disaster risk reduction in Dusun II Kalukau, West Sibalaya Village is one of the efforts to provide direct education informally to the community. This study aims to produce information about public understanding and awareness of disaster risk reduction. This research was conducted with a qualitative approach. Data sources come from observation, discuccion focus groups, and active participation. The results showed that public understanding of disasters was relatively good, the implementation of disaster risk reduction socialization was considered good as an educational effort for disaster mitigation.